Кровососущие комары Николаевской области и некоторых смежных территорий - Прендель, А.Р.; Анцибор, С.С.; Коренчевская, Г.А. (Вестник зоологии, 1967)
22 species and subspecies of Culicidae are registered in Nikolayev region until now.. They are: Anopheles — 6, Theobaldia — 1, Uranotaenia —1, Taeniorynchus — 1, Aedes — 8, Culex — 5. It is necessary to note among the flies of Nikolaev region the Anopheles algeriensis which was grown from the larva found in the South Bug. This species is observed for the first time in the Ukraine. The Uranotaenia unguiculata which was found in Golovanevsk, was pointed out for rice fields in the suburbs of Voznesensk; Culex hortensis was found in Pervomaisk for the first time. The rest 19 species are the usual species of Culicidae, typical for the steppe zone of the Ukraine.